Fostering environmental democracy in Latin America and the Caribbean: An analysis of the Regional Agreement on Environmental Access Rights. Issue 2 (7th February 2019) - Olmos Giupponi, Belén
Abstract : Principle 10 of the 1992 Rio Declaration laid the groundwork for the implementation of access to environmental information, public participation and access to environmental justice, which constitute the three pillars of environmental democracy. The 2012 United Nations Conference on Sustainable Development marked a turning point in this evolution as Latin American and Caribbean (LAC) countries launched the negotiations for a treaty embodying these environmental rights. This process resulted in the adoption of the Regional Agreement on Environmental Access Rights (RAEAR) in March 2018. This presents a unique opportunity to reflect not only on the RAEAR but, more broadly, on the implementation of environmental rights in international environmental law. The article first addresses the question of the delayed implementation of environmental democracy rights in LAC. It then critically analyses the RAEAR provisions and the lessons to be learned from the negotiations. Finally, the article underlines outstanding challenges in the implementation.